2021
DOI: 10.1177/22786821211000190
|View full text |Cite
|
Sign up to set email alerts
|

Learning Beyond the Brick and Mortar: Prospects, Challenges, and Bibliometric Review of E-learning Innovation

Abstract: The increasing proliferation of IT services in all sectors has reinforced the adoption and diffusion across all levels of education and training institutions. However, lack of awareness, knowledge about the key challenges, and opportunities of e-learning seem to allude policymakers, resulting in low adoption or increased failure rate of many e-learning projects. Our study tries to address this problem through a review of relevant literature in e-learning. Our goal was to draw from the existing literature, insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
(145 reference statements)
0
0
0
Order By: Relevance
“…A study examining trends in the affective use of computing in a range of e-learning environments-including education [30] that was based upon a corpus of 27 papers. The study defines e-learning as ".…”
Section: Scoping Review-discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study examining trends in the affective use of computing in a range of e-learning environments-including education [30] that was based upon a corpus of 27 papers. The study defines e-learning as ".…”
Section: Scoping Review-discussionmentioning
confidence: 99%
“…The authors in Ref. [30] found these environments were the most popular because they relied upon conversational language where emotion can occur and therefore can be detected with affective computing systems. Though this SLR also found that affective computing was not exploited as much as it could have been within the research that was analysed.…”
Section: Scoping Review-discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…al., 2022). Moreover, research has addressed potential barriers to effective self-evaluating ability, such as lack of metacognitive awareness and limited opportunities for reflection (Ceesay, 2021;Yousef, et. al.,2023).…”
mentioning
confidence: 99%